Ischemic patterns and their angiographic risk factors in adult patients with moyamoya disease - Si Luo; Wenjie Zhan; Lanjiao Zhang; Chenying Zeng; Daojun Hong; Pu Fang; Qianxi Chen; Jing Lin (Annals of Clinical and Translational Neurology, 2023)
Abstract Objective The present study aims to determine whether angiographic differences increase the risk of ischemic pattern among adult patients with moyamoya disease (MMD). Methods From January 2020 to December 2021, we retrospectively enrolled 123 ischemic or asymptomatic adult patients diagnosed as MMD. Angiographic changes including Suzuki stage, moyamoya vessels, anterior choroidal artery (AChoA) dilatation, lenticulostriate artery (LSA) dilatation, posterior communicating artery (PcomA) dilatation, and posterior cerebral artery (PCA) involvement were evaluated for all patients. Results Among the 123 participants, 35 ischemic patients and 88 asymptomatic patients were analyzed. There was no significant difference of Suzuki stage, AChoA dilatation, LSA dilatation, and PcomA dilatation between ischemic group and asymptomatic group. The grading of moyamoya vessels differed significantly but was not a factor associated with ischemic pattern after adjusting multiple related confounders. However, the frequency of PCA steno‐occlusive changes in ischemic patients was statistically higher than that in asymptomatic patients (54.3% vs 34.1%, p = 0.039). Furthermore, PCA involvement was a risk factor associated with ischemic form and remained statistically significant after the multivariate adjustment (p = 0.033, 95% CI 1.092–8.310). Interpretation PCA involvement is closely related to the presentation of ischemic stroke but other angiographic features had no association with ischemic pattern in adult MMD.